2020
DOI: 10.1515/cclm-2020-1170
|View full text |Cite
|
Sign up to set email alerts
|

Choice of faecal immunochemical test matters: comparison of OC-Sensor and HM-JACKarc, in the assessment of patients at high risk of colorectal cancer

Abstract: ObjectivesCurrently, NICE recommends the use of faecal immunochemical test (FIT) at faecal haemoglobin concentrations (f-Hb) of 10 μg Hb/g faeces to stratify for colorectal cancer (CRC) risk in symptomatic populations. This f-Hb cut-off is advised across all analysers, despite the fact that a direct comparison of analyser performance, in a clinical setting, has not been performed.MethodsTwo specimen collection devices (OC-Sensor, OC-S; HM-JACKarc, HM-J) were sent to 914 consecutive individuals referred for fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…5 To date there are only two peer-reviewed publications that have directly compared results obtained on two different FIT analytical systems when patients have taken samples from the same bowel motion in a symptomatic pathway. 75 101 In the first study 75 732 patients returned both an OC-Sensor and an HM-JACKarc collection device. They had been instructed to collect samples into each device from the same bowel motion.…”
Section: Grade Of Evidence: Low; Strength Of Recommendation: Weakmentioning
confidence: 99%
See 2 more Smart Citations
“…5 To date there are only two peer-reviewed publications that have directly compared results obtained on two different FIT analytical systems when patients have taken samples from the same bowel motion in a symptomatic pathway. 75 101 In the first study 75 732 patients returned both an OC-Sensor and an HM-JACKarc collection device. They had been instructed to collect samples into each device from the same bowel motion.…”
Section: Grade Of Evidence: Low; Strength Of Recommendation: Weakmentioning
confidence: 99%
“…A meta-analysis to inform the guidelines identified seven studies (n=18 264) that used the NG12 definition of symptomatic patients and colonoscopy or CTC as the reference standard 14 51 62 72 75–77. The summary estimates of sensitivity and specificity were 88.7% (95% CI 84.4% to 92.0%) and 78.5% (95% CI 73.0% to 83.2) at a cut-off of 10 µg/g.…”
Section: Diagnostic Accuracy Of Fit For Crc In People With Suspected ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines for colorectal cancer screening in Japan only recommend the two-sample FIT as standard, with no specific kits or cut-off values. As differences in FIT kit features and thresholds have been known to affect screening performance, 29 these variations are certainly a limitation of our study. However, a notable difference in the results between two-positive and one-positive FIT groups shown in our study suggests a common trend irrespective of kits brand.…”
Section: Discussionmentioning
confidence: 99%
“…Godber et al reported a significant lower sensitivity of 68.9% and a specificity of 80.2% using a cutoff of 10 μg/g [ 23 ]. Further, Chapman et al [ 27 ] reported a sensitivity of 84% and a specificity of 78% in patients with increased risk of CRC.…”
Section: Discussionmentioning
confidence: 99%